Involvement of junctional adhesion molecules in lymphatic vascular remodelling in rheumatoid arthritis. (22nd February 2011) - Milia, A F; Manetti, M; Pfanner, S; Nacci, F; Fiori, G; Guiducci, S; Romano, E; Ceccarelli, C; Ibba-Manneschi, L; Matucci-Cerinic, M
Abstract : Background and objective: Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease, in which neovascularisation of the synovium is regarded as a crucial step in its development and progression. Lymphatic neovascularisation has been observed in RA joints. Junctional adhesion molecule A (JAM-A) and JAM-C regulate leucocyte-endothelial cell (EC) interactions. JAMs also interact at inter-EC junctions regulating vascular permeability and are implicated in pathophysiological processes involving leukocyte transmigration, tight junction assembly and angiogenesis. The aim of this study was to investigate the role of JAM-A and JAM-C in mediating the lymphoangiogenic process in RA synovium. Materials and methods: Synovial biopsies from RA and osteoarthritic (OA) patients, used as control, has been collected during arthroplasty or synovectomy. Synovial sections were stained with primary antibodies (Abs) antihuman JAM-A or JAM-C followed by fluorochrome-conjugated secondary Abs. The lymphatic EC specific marker podoplanin (D2-40) was used to differentiate blood (D2-40−) and lymphatic (D2-40+) vessels. Results: Immunohistochemical analysis showed, in RA synovium, the presence of abundant D2-40+ structures, identifiable as lymphatic vessels. Many D2-40+ cells were also found in the intimal lyning layer, specially in the hyperplasic areas. Lymphatic vessels were distributed in the sublining, specially around blood vessels. Clusters of D2-40+ cells were also found in the inflammatory infiltrate, in structures resembling new lymphatic vessels. In all sections from RA, JAM-A and JAM-C were observed on almost all vasculature including the lymphatic (D2-40+) and blood vessels (D2-40−). Initial lymphatic vessels reacted with anti-JAM-A and anti-JAM-C. In the synovial lining, JAM-A and JAM-C were expressed on D2-40+ macrophage-like synoviocites. D2-40+ cells in the inflammatory infiltrate showed positivity for both JAM-A and JAM-C. The immunostaining for both JAMs was weaker in OA than in RA synovium. Conclusion: This results confirm the presence of an increased number of lymphatic vessels in RA synovial tissue. Moreover, the authors observed D2-40+ structures, mostly around pre-existing blood vessels, indicating the development of a new lymphatic network in the synovial sublining. The presence of D2-40+ cells in the inflammatory infiltrate and in the macrophage-like synoviocites, lead us to hypothesise that in RA, macrophages are activated and may function as lymphatic precursors. In RA synovium, both JAM-A and JAM-C are expressed in all D2-40+ cells, indicating their participation in the inflammatory process and intercellular junction assembly. Their expression in new lymphatic vessels and in D2-40+ cells stimulated to form new vessels, confirm their involvement in the lymphoangiogenic process occurring in RA.